Engraving of Firearms Ornament - Claude Simonin (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Engraving of Firearms Ornament. French | Engraving | Works on Paper-Prints
Droits : Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie